2015
DOI: 10.4172/2155-6105.1000252
|View full text |Cite
|
Sign up to set email alerts
|

Confounding of the Comparative Safety of Prenatal Opioid Agonist Therapy

Abstract: Prenatal opioid agonist therapy with methadone or buprenorphine prevents maternal illicit opioid use and withdrawal and improves pregnancy outcomes compared to heroin use alone. Historically, methadone has been the first-line opioid agonist therapy for pregnant opioid dependent women; in recent years buprenorphine has become first-line treatment for some opioid dependent pregnant women. While there is some evidence of better outcomes in neonates exposed to buprenorphine vs. methadone, the effect of confounding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…performed an adjusted analysis the differences disappeared 11. Indeed, only few studies comparing the safety of B versus M on the neonate adjust for confounding 39.…”
Section: Discussionmentioning
confidence: 99%
“…performed an adjusted analysis the differences disappeared 11. Indeed, only few studies comparing the safety of B versus M on the neonate adjust for confounding 39.…”
Section: Discussionmentioning
confidence: 99%
“…Potential confounding by indication can occur in assessing the comparative outcomes of prenatal BMT versus MMT because maternal characteristics that might influence choice of prenatal treatment with BMT versus MMT likely also affect neonatal outcomes [13, 14]. Prior studies have suggested improved NAS and birth outcomes in neonates exposed to buprenorphine compared to methadone, including decreased NAS severity with shorter length of hospitalization, lower risk of NAS pharmacologic treatment, and higher gestational age at birth, birth weight, body length and head circumference [1517].…”
Section: Discussionmentioning
confidence: 99%
“…However, differences in pregnancy outcomes between women treated with methadone vs. BPN need to be considered in light of the possible role of unmeasured confounding. For example, the choice of opioid agonist therapy may be influenced by maternal characteristics, including comorbidities, continued illicit opioid use, or concurrent use of psychotropic medications . Regardless of whether methadone or BPN is prescribed, clinicians treating pregnant women with opioid dependence should be mindful of the high prevalence of psychiatric comorbidities in this population, as increased severity of NAS has been observed with concurrent exposure to benzodiazepines and antidepressants …”
Section: Methodsmentioning
confidence: 99%